LEGAL PROTECTION AGAINST UNAUTHORISED USE OF CULINARY ACCOUNT VIDEOS ON THE INSTAGRAM PLATFORM - Primalianda, Ayu Tri; Kuspraningrum, Emilda; Hediati, Febri Noor (Jambura Journal Civic Education, 2025)
The aim of this research is to explore the legal safeguards against theunauthorized use of culinary account videos on Instagram. Asdigitalization and social media content distribution trends grow, theunauthorized reuse of culinary videos without the original owner'sconsent is becoming more prevalent, raising concerns aboutcopyright and the legal standing of content creators. This studyemploys a doctrinal research approach, utilizing normative legalresearch methods through statutory and conceptual frameworks.The research draws on primary legal materials, including LawNumber 28 of 2014 on Copyright, Law Number 1 of 2024 amendingLaw Number 11 of 2008 on Electronic Information and Transactions,and Law Number 24 of 2019 on Creative Economy. Additionally,secondary legal materials were sourced from legal journals, books,and Instagram's internal policy documents related to intellectualproperty rights and digital content usage. The findings indicate thatvideos created and posted by culinary accounts are classified asvideographic works, thus receiving legal protection under LawNumber 28 of 2014 on Copyright. Provisions in Law Number 1 of2024 and Instagram's internal policies further reinforce the legalprotection for culinary content creators against unauthorized use.However, in practice, violations frequently occur due to low userawareness, commercial interests in culinary content, and ineffectivereporting mechanisms on the platform. Consequently, the existinglegal protection is not fully optimal and requires enhancement inboth regulatory and implementation aspects.